2022
DOI: 10.1007/s00284-022-03064-4
|View full text |Cite
|
Sign up to set email alerts
|

The Faecal Microbiome of the Wild European Badger Meles meles: A Comparison Against Other Wild Omnivorous Mammals from Across the Globe

Abstract: Here we investigate the faecal microbiome of wild European badgers Meles meles using samples collected at post-mortem as part of the All Wales Badger Found Dead study. This is the first published characterisation of the badger microbiome. We initially undertook a sex-matched age comparison between the adult and cub microbiomes, based on sequencing the V3–V4 region of the 16S rRNA gene. Analysis used the QIIME 2 pipeline utilising DADA2 and the Silva database for taxonomy assignment. Fusobacteria appeared to be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Faecal microbiome analysis of live trapped badgers would be useful to help corroborate any shifts in gut microbiota associated with altered tyrosine metabolism, which could be the cause of signi cant differences in gut derived metabolites (such as the phenylsulfates) observed in this study. A previous study of the faecal microbiome of badgers, involving samples collected from road-killed badgers showed that in bTB negative badgers the microbiome was distinct from that observed in other wild, omnivorous mammals [41].…”
Section: Discussionmentioning
confidence: 87%
“…Faecal microbiome analysis of live trapped badgers would be useful to help corroborate any shifts in gut microbiota associated with altered tyrosine metabolism, which could be the cause of signi cant differences in gut derived metabolites (such as the phenylsulfates) observed in this study. A previous study of the faecal microbiome of badgers, involving samples collected from road-killed badgers showed that in bTB negative badgers the microbiome was distinct from that observed in other wild, omnivorous mammals [41].…”
Section: Discussionmentioning
confidence: 87%